Frequency of placenta previa in previously scarred and non scarred uterus - Majeed, Tayyaba (Pak J Med Sci, 2015)
OBJECTIVE: To determine the frequency of placenta Previa in patients coming to a tertiary care unit with previously scarred and non-scarred uterus. METHODS: A descriptive cross sectional study was carried on 114 cases who underwent caesarean sections (37 cases out of 645 cases with non scarred uterus and 77 cases from 721 cases with scarred uterus) in the department of obstetrics and gynecology Lady Willingdon Hospital from January 2008– December 2011. RESULTS: Most patients (47.36%) were between 26-30 years age group, presented with gestational age between 36-40 weeks (70.17%), were mostly G2-4, while frequency of placenta Previa in non-scarred uterus was 32.45% (37 cases), and frequency in previously scarred uterus was 67.54% (77 cases). Major degree Previa was found in 88 cases (77.19%). There were 5.70% cases of placenta Previa from non-scarred uteruses and 10.67% cases of placenta Previa (10.67%) from already scarred uteruses. Stratification revealed a higher trend of the morbidity with the increase in number of previous caesarean sections. CONCLUSION: A significantly higher frequency of placenta Previa was found among patients coming to a tertiary care hospital with previously scarred uterus.